Further studies on the biological activity of hazelnut allergens. Issue 1 (17th July 2015) - Blanc, F.; Bernard, H.; Ah‐Leung, S.; Przybylski‐Nicaise, L.; Skov, P. Stahl; Purohit, A.; de Blay, F.; Ballmer‐Weber, B.; Fritsche, P.; Rivas, M. Fernandez; Reig, I.; Sinaniotis, A.; et al.
Abstract: Background: Sensitization to hazelnut allergens vary depending on the geographic origin and age of the patients. The objective of this study was to further investigate the allergenic activity of hazelnut allergens using sera from patients recruited in various European regions and presenting different sensitization patterns to hazelnut proteins. Methods: Natural Cor a 11 and Cor a 9 were purified from hazelnut whereas Cor a 1 and Cor a 8 were produced as recombinant proteins (rCor a 1.04 and rCor a 8). Sera from hazelnut allergic patients were collected in France ( n  = 5), Switzerland ( n  = 2), Greece ( n  = 11) and Spain ( n  = 3), within the Europrevall project. Total and allergen‐specific IgE were quantified by enzyme allergosorbent test and IgE immunoblot were performed using pooled sera from birch‐pollen endemic region or from Greece. Histamine Release (HR) assays were performed with stripped basophils passively sensitized with individual sera and challenged by a hazelnut extract or the different hazelnut allergens. Results: As previously described, hazelnut allergic patients from Mediterranean countries are mainly sensitized to the nsLTP Cor a 8 whereas patients from France and Switzerland are sensitized to pollen‐related allergens. Interestingly, an intermediate profile was evidenced in patients from Madrid. Hazelnut 7S globulin (Cor a 11) and 11S globulin (Cor a 9) were found to be minor allergens, recognized only by patients from Mediterranean countries. The biologic activity of the 4 tested allergens, analysed by HR assay, further confirmed the sensitization patterns, but also demonstrated the very high elicitation potency of Cor a 8. Conclusions: This work, extending previously published researches, represents a step towards the better understanding of the complexity of hazelnut allergy and provides new data on the biological activity of hazelnut allergens and extracts.